2022
DOI: 10.1029/2022jc018960
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Estuarine Total Exchange Flow From Discrete Observations

Abstract: The exchange between estuaries and the coastal ocean is a key dynamical driver impacting biogeochemical patterns such as nutrient and phytoplankton concentrations within the estuary (e.g., Boyer et al., 2002;Brown & Ozretich, 2009) and in the coastal ocean (e.g., Davis et al., 2014). This exchange can regulate estuarine residence time, hypoxia, and acidification (e.g., MacCready et al., 2021;O'Callaghan et al., 2007). Estuaries deliver terrigenous material to the ocean including sediment, larvae, and pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Due to the recent invention of the theory, TEF has only been applied to numerical model output. However, a recent paper by Lemagie et al (2022) suggested how TEF may be measured with field observations.…”
Section: Quantifying Numerical Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the recent invention of the theory, TEF has only been applied to numerical model output. However, a recent paper by Lemagie et al (2022) suggested how TEF may be measured with field observations.…”
Section: Quantifying Numerical Mixingmentioning
confidence: 99%
“…However, a recent paper by Lemagie et al. (2022) suggested how TEF may be measured with field observations.…”
Section: Introductionmentioning
confidence: 99%
“…TEF is only one of several estuarine salt flux decompositions we could have used (Chen et al., 2012; Garcia & Geyer, 2023; Geyer & MacCready, 2014; Lemagie et al., 2022). The advantage of TEF, especially in the budget (4), is that it allows separate consideration of the exchange flow, here taken as synonymous with Q in , and the salinity difference it acts on, Δ S .…”
Section: Introductionmentioning
confidence: 99%